Stenotrophomonas maltophilia complex: insights into evolutionary relationships, global distribution and pathogenicity - Li, Kun; Yu, Keyi; Huang, Zhenzhou; Liu, Xiao; Mei, Li; Ren, Xiaodong; Bai, Xuemei; Gao, He; Sun, Zhiwen; Liu, Xiaoning; Wang, Duochun (Frontiers in Cellular and Infection Microbiology, 2024)
Stenotrophomonas maltophilia complex (Smc) comprises opportunistic Gram-negative bacilli responsible for various human-related infections. Despite its clinical relevance, limited data exists concerning its evolutionary lineage, global prevalence and pathogenicity. In this study, we conducted an extensive genomic analysis on 734 Smc genomes, of which 90 were newly sequenced. Phylogenetic analyses delineated 24 species-level clades, dominated by S. maltophilia (42.8%), S. sepilia (13.6%) and S. geniculata (9.9%). Geographically, strains were primarily distributed in Europe (34.2%), Asia (33.7%) and North America (24.0%). Some differences observed across continents in the distribution of Smc reveal intricate global distribution patterns.Meanwhile, 154 virulence-associated genes and 46 antimicrobial resistance genes within Smc were identified. These genes encode span various functions, including motility, adherence, toxin, RND antibiotic efflux pumps, beta-lactamases and aminoglycoside-modifying enzymes. Such a genetic repertoire implies sophisticated strategies employed by Smc for host invasion and self-preservation. Furthermore, significant variations were indicated in swimming motility and biofilm formation capability across the different species of Smc, with S. sepilia exhibiting superior levels of both traits, indicative of elevated pathogenic potential. Regarding antibiotic susceptibility, no statistically significant discrepancy was detected among Smc species to other antibiotics, despite the fact that all S. geniculata isolates were resistant to Ceftazidime and much higher than other species. Collectively, our study contributes valuable insights into the phylogeny, global distribution and clinical pathogenic potential of Smc, which are crucial for better managing Smc-related infections and tailoring effective treatment strategies.